Reductive Etherification of Aldehydes and Ketones with Alcohols and Triethylsilane Catalysed by Yb(OTf)3: an Efficient One‐Pot Benzylation of Alcohols. Issue 19 (16th August 2019) - Pelosi, Azzurra; Lanari, Daniela; Temperini, Andrea; Curini, Massimo; Rosati, Ornelio
Abstract: The one‐pot synthesis of symmetrical and unsymmetrical ethers from aldehydes and ketones can be conveniently performed using Yb(OTf)3 as catalyst and triethylsilane as reducing agent in presence of alcohols. This methodology leads to the synthesis of ether derivatives with good yields. Notably, this process resulted a useful tool to protect alcohols as benzyl ether derivatives using differently substituted benzaldehydes as protecting agents under mild conditions. A plausible mechanism was also proposed. Abstract :